The scope for multilateral international co-operation in tax affairs / The tax and exchange control consequences of virtual currency transactions in South Africa - Coelho, Andrew Satiro (Department of Finance and Tax, 2017)
1. The scope for multilateral international co-operation in tax affairs: While some measures have been taken in the past to create some form of multilateral co-operation in respect of the enforcement of domestic tax laws, these have been limited either in scope or in scale, or both. This paper seeks to analyse the various attempts at multilateralism, investigate the theoretical reasons behind the perceived dominance of bilateralism in tax relations, and assess the scope for potential multilateral issues in the international tax law environment. 2. The tax and exchange control consequences of virtual currency transactions in South Africa: There is seemingly little research on how virtual currencies might be affected by domestic tax laws, or whether there should be a new tax regime implemented specifically for virtual currencies. This paper looks at how virtual currencies fit into the South African legislature and tax authorities' current tax and exchange control regime, as well as the problems this presents. It then compares that stance to select foreign jurisdictions before arriving at a conclusion at how the problems faced in South Africa might be better resolved. This results in a finding that while legislative measures might need to be taken in the future, it might only be an urgent necessity for the purposes of Exchange Control.